Correcting the “correct” name for the Asian Brown Flycatcher (Aves: Passeriformes, Muscicapidae, Muscicapa) - Dickinson, Edward C.; Schodde, Richard; Kullander, Sven; Crochet, Pierre André; Elliott, Andy; Kirwan, Guy M. (Zootaxa, 2014)
Mlíkovský (2012) claimed that Muscicapa latirostris Raffles, 1822 was the correct name for the Asian Brown Flycatcher, and rejected its senior synonym, Muscicapa dauurica Pallas, 1811. Muscicapa dauurica is in equal or greater use today for this flycatcher, to which the references to it in Mlíkovský (2012) testify even though they are far from comprehensive. Other major references using dauurica Pallas are Sibley & Monroe (1990), Inskipp et al. (1996), Kennedy et al. (2000), Dickinson (2003), Rasmussen & Anderton (2005), Clement (2006), Wells (2007) and Mann (2008).